2015
DOI: 10.1002/cssc.201500945
|View full text |Cite
|
Sign up to set email alerts
|

A TiO2 Nanofiber–Carbon Nanotube‐Composite Photoanode for Improved Efficiency in Dye‐Sensitized Solar Cells

Abstract: A light-scattering layer fabricated from electrospun titanium dioxide nanofibers (TiO2 -NFs) and single-walled carbon nanotubes (SWCNTs) formed a fiber-based photoanode. The nanocomposite scattering layer had a lawn-like structure and integration of carbon nanotubes into the NF photoanodes increased the power conversion efficiency from 2.9 % to 4.8 % under 1 Sun illumination. Under reduced light intensity (0.25 Sun), TiO2 -NF and TiO2 -NF/SWCNT-based DSSCs reached PCE values of up to 3.7 % and 6.6 %, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Anatase is one of the mineral forms of titanium dioxide (TiO 2 ) that is extensively used in many energy [35,50,51] and selfcleaning [52,53] applications. Its tetragonal crystal symmetry with good stability makes anatase an excellent material for electrochemical Li storage that could result in applications related to Li-ion batteries.…”
Section: Anatase Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…Anatase is one of the mineral forms of titanium dioxide (TiO 2 ) that is extensively used in many energy [35,50,51] and selfcleaning [52,53] applications. Its tetragonal crystal symmetry with good stability makes anatase an excellent material for electrochemical Li storage that could result in applications related to Li-ion batteries.…”
Section: Anatase Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…[19] In addition, our group reportedr ecently the photocatalytic hydrogen evolution activities of CZTS, Cu 2 ZnSnSe 4 (CZTSe), andC u 2 ZnSnSe 4Àx S x (CZTSeS) nanofibers in the presence of triethanolamine( TEOA) as the sacrificial electron donor and eosin Y( EY) as the photosensitizer under visible-light irradiation (l > 420 nm). [17,19,27] Semiconducting nanowires, [28] nanofibers, [29][30][31] and nanotubes [31] are used to enhance charget ransport in different energy applicationss uch as photovoltaic devices and hydrogen evolution reactions. [20][21][22] However,i ti sq uite difficult to control the phase crystal structure of quaternary semiconductors and to explain their stoichiometries owing to the sophistication of the component materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by Habisreutinger et al has shown that SWCNTs can also be used as p‐type dopants in Spiro‐MeTAD to replace the common dopants 4‐tert‐butylpyridine (tBP) and the hydroscopic bis(trifluoromethane)sulfonimide lithium salt (LiTFSI) . Furthermore, the combination of two separate 1D materials, such as nanofibers and nanotubes, has also been shown to improve performance . CNTs can also be used in the ETL and despite this being somewhat counterintuitive when considering only the slightly p‐type character of the CNTs, this nevertheless results in clear improvements in overall device performance .…”
Section: Introductionmentioning
confidence: 99%
“…CNTs can also be used in the ETL and despite this being somewhat counterintuitive when considering only the slightly p‐type character of the CNTs, this nevertheless results in clear improvements in overall device performance . Previous reports have suggested that the CNTs could improve electron mobility and directionality; however; further research is required to fully understand the mechanism of this system. While clear evidence of improved charge transfer has been shown at the interface between pure SWCNT contacts and a methylammonium lead iodide (MAPbI 3 ) absorber layer, an understanding of the performance enhancement achieved when these two materials are combined as a composite material in PSCs is still lacking.…”
Section: Introductionmentioning
confidence: 99%